2001
DOI: 10.1254/jjp.85.271
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+ Exchange Inhibitor SM-20220 Improves Endothelial Dysfunction Induced by Ischemia-Reperfusion

Abstract: ABSTRACT-Endothelial cells play an important role in the physiologic homeostasis of the cerebral circulation. Previously, we showed that the Na + / H + exchanger (NHE) inhibitor SM-20220 (N-(aminoiminomethyl)-1-methyl-1H-indole-2-carboxamide methanesulfonate) improved ischemic brain injury. In this study, we investigated the effect of SM-20220 on cerebrovascular dysfunction after ischemia-reperfusion, focusing on the kinds of dysfunction that involved endothelial function. In cultured bovine brain microvascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Therefore, it is supposed that the protective effect of sabiporide on BBB dysfunction may be, at least partially, involved in its neuroprotective effect against ischemic injury, although we cannot clarify how much of this BBB protection will contribute to the sabiporide's effect on brain damage. Consistent with our results, SM-20220 which is known to protect neurons against excitotoxicity in rat cortex (Matsumoto et al, 2004) has shown a significant suppressing effect on Evans blue extravasation during cerebral ischemia (Horikawa et al, 2001). In addition, cariporide, a well known NHE-1 inhibitor preserving neuroprotective effects (Luo et al, 2005), also reduced S-100B release in serum during cardiac surgery, suggesting its protective effect on BBB permeability (Scholz et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, it is supposed that the protective effect of sabiporide on BBB dysfunction may be, at least partially, involved in its neuroprotective effect against ischemic injury, although we cannot clarify how much of this BBB protection will contribute to the sabiporide's effect on brain damage. Consistent with our results, SM-20220 which is known to protect neurons against excitotoxicity in rat cortex (Matsumoto et al, 2004) has shown a significant suppressing effect on Evans blue extravasation during cerebral ischemia (Horikawa et al, 2001). In addition, cariporide, a well known NHE-1 inhibitor preserving neuroprotective effects (Luo et al, 2005), also reduced S-100B release in serum during cardiac surgery, suggesting its protective effect on BBB permeability (Scholz et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that the protective effects of NHE-1 inhibitor on ischemic brain injury may be mediated, at least in part, by the prevention of endothelial dysfunction (Horikawa et al, 2001). Our results support this concept by showing the protective effect of sabiporide against BBB hyperpermeability in a rat brain ischemia model.…”
Section: Discussionmentioning
confidence: 99%
“…An amelioration of endothelial cell dysfunction after transient ischemia has been observed with NHE inhibition (37). NHE inhibition was also associated with reduced blood-brain barrier disruption, improved postischemic perfusion, and neuroprotection (37).…”
Section: Discussionmentioning
confidence: 99%
“…An amelioration of endothelial cell dysfunction after transient ischemia has been observed with NHE inhibition (37). NHE inhibition was also associated with reduced blood-brain barrier disruption, improved postischemic perfusion, and neuroprotection (37). In astrocyte cultures, oxygen and glucose deprivation resulted in a large increase in intracellular sodium and an increase in cell volume (10).…”
Section: Discussionmentioning
confidence: 99%
“…immediately after initiation of ischemia) reduced total infarction area by ~50%, and partially prevented formation of brain edema [96]. These effects may be relevant to preservation of blood-brain barrier function and improved reperfusion rates [97], as well as to reduced accumulation of leukocytes in damaged brain tissue [98]. In the same model, another selective NHE blocker, sabiporide (3 mg/kg, i.v.…”
Section: Pathological Roles For Na + /H + Exchange: Impact On [Na + ]mentioning
confidence: 95%